Meningkatkan Kompetensi Profesional Guru Dalam Pembuatan Unit Kegiatan Belajar Mandiri (UKBM) Melalui SEPEV Pada MGMP Mini Di MAN 2 Kota Probolinggo Semester Genap Tahun Ajaran 2018/2019 - Makmur, Mohammad Alfan (Inovasi: Jurnal Diklat Keagamaan, 2020)
Learning activities are carried out to direct children to be able to learn in an interactive, inspiring, fun, challenging, and motivating way to actively participate in achieving basic competencies (KD). Teachers as educators have the main task of organizing learning activities that should be carried out effectively. To get the effectiveness of the learning process and to create superior madrasas, programs can be realized, one of which is increasing the professional competence of teachers in making UKBM through Sepev on mini MGMP. Therefore, the researcher formulated the problem of how to improve the process of teachers’ professional competence in making UKBM through SEPEV at Mini MGMP, and how to improve the results of teacher Professional Competence in making UKBM through SEPEV in Mini MGMP Madrasah Aliyah Negeri 2 Probolinggo Academic Year 2018/2019. The results of this study were an improvement in the process, namely the score of the observation results showed that from 64 teachers that there was an increase starting from the pre-cycle, the first cycle (66.7%), and the second cycle (89.2%) and the questionnaire results showed that from 64 teachers in cycle I there were 10 teachers (15.6%) who answered “YES” and there were 54 teachers (84.4%) who answered "NO". Meanwhile, in cycle II there were 55 teachers (85.9%) who answered "YES" and there were 9 teachers (14.1%) who answered "NO". From these data, it shows that the Improvement of Teacher Professional Competence in Making UKBM through the Week of Evaluation Method (SEPEV) at Mini MGMP which is held every Saturday simultaneously at 10.00-13.00 WIB in MAN 2 Probolinggo City has been achieved.